Revitalisasi Pasar Rukun Masyarakat (Parukmas) dengan Inovasi Fasilitas Spot Foto Instagramable untuk Pengembangan Wisata Kreatif di Yosodadi Kecamatan Metro Timur - Iswati Iswati; Bayu Ardiwansyah; Retno Fajarwati; Faizah Kanti Pandia; Handini Lutfiana Alfaqih (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
The revitalization of the Rukun Masyarakat (Parukmas) Market through innovative Instagrammable photo spots is a strategic effort to develop the potential for creative tourism in Yosodadi Village, Metro Timur District. The market, which previously served only as a center of local economic activity, is being revitalized into a public space-based tourist destination that is aesthetic, educational, and attractive. This transformation aims to create a new experience for visitors by presenting an engaging, thematic visual design that aligns with social media trends, particularly Instagram. This research aims to design and implement Instagrammable photo spots that can enhance the appeal of Parukmas Market and evaluate their impact on increasing visitor numbers and empowering the surrounding community economically. The research method used is participatory, involving the community, vendors, and local stakeholders in the planning, design, and construction of the facility. Evaluation is conducted through direct observation of market activities and visitor satisfaction surveys to assess responses and perceived benefits. The expected outcome of this activity is the creation of a creative space that can enhance social interaction, strengthen local identity, attract tourists, and open new business opportunities for the community, thereby strengthening the local economy and increasing vendor income.